2015
DOI: 10.1016/j.jnci.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunohistochemical expression of β-catenin, EGFR, ErbB2, and p63 in adamantinomatous and papillary craniopharyngiomas

Abstract: Nuclear accumulation of β-catenin is a diagnostic hallmark of the ACP and is very helpful in the differential diagnosis between both ACP and PCP in the setting of small biopsies. Moreover, the restricted nuclear β-catenin accumulation in the cohesive cell clusters within the whorl-like areas supports that aberrant β-catenin expression may play a role in the morphogenesis of ACP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
1
19
0
2
Order By: Relevance
“…In the limited molecular studies to date, increased expression of proliferation markers and TP53 have been observed in malignantly transformed specimens as well as in some rapidly recurring tumors. 25,41 While TP53 expression appears to be rare in nontransformed ACP, its related family member TP63 is widely expressed, particularly the deltaNp63 isoform 11,14,37 translating the therapeutic Opportunities and Challenges Ahead…”
Section: Molecular Biology Of Tumor Recurrencementioning
confidence: 99%
“…In the limited molecular studies to date, increased expression of proliferation markers and TP53 have been observed in malignantly transformed specimens as well as in some rapidly recurring tumors. 25,41 While TP53 expression appears to be rare in nontransformed ACP, its related family member TP63 is widely expressed, particularly the deltaNp63 isoform 11,14,37 translating the therapeutic Opportunities and Challenges Ahead…”
Section: Molecular Biology Of Tumor Recurrencementioning
confidence: 99%
“…9,11,12,24,28,38 As a result of this mechanism, nuclear accumulation of b-catenin is a histological hallmark of CTNNB1 mutation. 10,12,16,26,41 In the case of craniopharyngiomas, mutation of CTNNB1 has been described in 69%-100% 9,20,28 of ACP specimens, while it is not routinely observed in PCP or other parasellar tumors. 9,28 In the most detailed study to date, CTNNB1 mutation was identified in 95% of ACP specimens, using massively parallel sequencing and targeted genotyping.…”
Section: Ctnnb1 Mutationmentioning
confidence: 99%
“…10,32 This protein plays a critical role in development, cellular proliferation, differentiation, and cell migration. 10,11,16,41 A destruction complex restrains b-catenin within the cytosol and facilitates its ubiquitination and proteasomal degradation. 31 The Wnt protein family includes approximately 20 different proteins that bind to the Frizzled (Fz) family of receptors.…”
mentioning
confidence: 99%
See 2 more Smart Citations